Keterampilan bermain bola voli pada peserta seleksi pekan olahraga pelajar daerah - Salsabila, Putri Hawa; Achmad, Irfan Zinat; Gani, Ruslan Abdul (Jurnal Porkes, 2023)
The purpose of this study was to determine the skills of playing volleyball in the selection participants of the regional student sports week (POPDA). Descriptive quantitative research approach. This research method is a survey with a volleyball playing skills test. The population of all POPDA selection participants amounted to 172 people. The sample was taken with simple random sampling technique, totaling 120 people consisting of setter 30, libero 16, middle block 34, opposite 16, and outside hitter 34. The results of the study of volleyball playing skills of POPDA selection participants were in the "good enough" category as much as 45%. The skill of playing the setter position is in the "not good" category as much as 50%. The playing skills of the libero position are in the "good" and "good enough" categories as much as 38%. The skill of playing the middle block position is in the "good enough" category as much as 41%. The skill of playing the opposite position is in the "good enough" category as much as 38%. The skill of playing the outside hitter position is in the "good enough" category as much as 35%. The conclusion is that playing skills are a combination of basic techniques, tactics, and strategies, participants must improve basic techniques and also tactics and strategies need to be honed again.